Evaluasi Penggunaan Antibiotik Dengan Metode Gyssens Pasien Demam Tifoid Rawat Inap di RSUD Dr. Soedono Madiun Tahun 2019-2020 - Sawitri, Satwika Budi; Fatihah, Nadia Iha; Istiqomah, Annis; Rahardjoputro, Rolando (Parapemikir : Jurnal Ilmiah Farmasi, 2025)
Typhoid fever is an acute infection of the digestive tract caused by Salmonella typhi bacteria. The main therapy for typhoid fever is the administration of antibiotics. The high incidence of typhoid fever in Indonesia has led to increased antibiotic use and triggered antibiotic resistance. Antibiotic resistance will cause various problems such as incurability of the disease, suprainfection, increased risk of side effects, mortality, morbidity and health costs. This study aims to determine the pattern of antibiotic use and evaluate the rationality of antibiotic use in typhoid fever patients at RSUD Dr. Soedono Madiun qualitatively using the Gyssens method. This study uses a qualitative descriptive method by collecting patient medical records retrospectively with a purposive sampling method. The obtained medical records will be analyzed qualitatively using Gyssens criteria. The results of the qualitative analysis show that from 57 medical records there are 14 types of antibiotics used with thiamphenicol as the most common antibiotic (22%). The results of the qualitative analysis are antibiotic prescriptions for typhoid fever at Dr. Soedono Madiun Regional General Hospital. Soedono Madiun is in accordance with 72% accuracy, namely category IV A as many as 9 (15%), category IV B as many as 2 (4%), category IV D as many as 5 (9%), category III B as many as 9 (15%), category II A as many as 1 (2%), category II B as many as 4 (7%), category I as many as 1 (2%) and category 0 as many as 26 (46%).